2019
DOI: 10.1016/j.jclepro.2019.01.050
|View full text |Cite
|
Sign up to set email alerts
|

Can money always talk? Implication for environmental compensation by international agribusiness

Abstract: With the development of agricultural industrialization, the environmental issues of intensive animal farming are attracting increasing attention. Using survey data from 313 Chinese households living near the large-scale broiler farms of an international food company, this paper employs a contingent valuation method and discrete choice experiment to quantify the willingness to accept an air pollution compensation scheme. We find the following. (1) 42% of respondents have a nonmonetary preference for compensatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The socio-economic variables include individual characteristics and household characteristics. Studies have shown that gender, age, education, family size, and income play a critical role in consumption decisions [14,48]. The individual characteristics are measured by the gender, age, and education attainment of each respondent.…”
Section: Data and Summary Statisticsmentioning
confidence: 99%
“…The socio-economic variables include individual characteristics and household characteristics. Studies have shown that gender, age, education, family size, and income play a critical role in consumption decisions [14,48]. The individual characteristics are measured by the gender, age, and education attainment of each respondent.…”
Section: Data and Summary Statisticsmentioning
confidence: 99%